Strategies for Enhancing the Resilience of Tourism Villages in Madura Using the House of Risk (HOR) Approach: Strategi Peningkatan Ketahanan Desa Wisata di Madura dengan Menggunakan House of Risk (HOR) - Agustina, Fitri; Pramudea, Helen Intan; Cahyadi, Indra; Anna, Ika Deefi (PROZIMA (Productivity, Optimization and Manufacturing System Engineering), 2025)
Tourist villages are villages with distinctive traditions, arts, culture and customs passed down from generation to generation which are used as tourist attractions by local residents. The Central Bira Tourism Village with Lon Malang Beach is included in the advanced tourist village category according to jadesta.kemenparekraf.go.id. Based on the results of observations, the management of the Tourism Village has not thought about plans and strategies regarding further development related to the Tourism Village, it has only focused on improving infrastructure, there has not been a plan for further development of the tourism village which has the potential to create risks, and there is a need for strategies to deal with the emergence of these risks. Risk analysis and risk mitigation to prevent risks and disturbances that are likely to arise in tourism village development activities. Risk analysis and determining risk mitigation strategies using the House of Risk method which consists of two implementation stages. The first stage is to identify the risk event, and the cause of the risk, then an assessment of the severity and occurrence values is carried out, followed by providing a correlation assessment of the relationship between the risk event and the cause of the risk. The results of the correlation assessment obtain an Aggregate Risk Potential value. In the second stage, using the Pareto concept, 15 risk agents were identified based on the results of the top ranking, mitigation strategies were used by the tourism village to overcome risks to tourism management activities.